Factors influencing turnover intention among private institution lecturers in Klang Valley - Anbalagi, Paramasivam (2021)
The main objective of this study is to identify the relationship between job satisfaction, organizational commitment, compensation, training and development to turnover intention. The questionnaire was distributed to the targeted respondents using the online method due to the Conditional Movement Control Order (CMCO) period. A total of 391 responses were received. However, only 375 responses are usable. The data analyzed by using the Statistic Package for Social Sciences (SPSS) for descriptive, correlation and regression analysis. The results show that organizational commitment is the most influential variable, followed by job satisfaction and compensation. However, training and development program is not related to turnover intention.